The Influence of Product Quality, Price, Product Innovation and Brand Image on Purchasing Decisions of Instant Noodles in Indonesia - Eka Nur Hidayah; Ginanjar Rahmawan (Kusuma Negara Business School, 2021)
This research is motivated by data showing an increase in sales of indofood instant noodles. For this reason, researchers conducted research to see the effect of product quality, price, product innovation, and brand image on purchasing decisions for indomie instant noodles in Boyolali. Purposive Sampling is a method used in research with a sample size of 50 respondents. The data were processed using the Statistical Package for Social Sciences (SPSS). The results of the data analysis research explained that simultaneously and partially product quality, price, product innovation and brand image influence purchasing decisions. The coefficient of determination (R) of 0.729 means that product quality, price, product innovation and brand image are closely related to purchasing decisions and Adjusted R Square (R2) is 0.531 or 53.1%.